2017
DOI: 10.1186/s13020-017-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Advances in bio-active constituents, pharmacology and clinical applications of rhubarb

Abstract: Rhubarb is one of the most ancient, commonly used and important herbs in Chinese medicine. The modern researches of rhubarb clarified the efficacies, ingredients and mechanisms in a more scientific and rigorous way. The main chemical compositions of rhubarb include anthraquinones, anthrones, stilbenes, tannins, polysaccharides etc. These compositions show extensive pharmacological activities including regulating gastrointestinal, anticancer, antimicrobial, hepatoprotective, anti-inflammatory, protecting cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(106 citation statements)
references
References 32 publications
0
98
0
2
Order By: Relevance
“…The antibacterial activity of BTS is one possible mechanism. Among BTS components, Menthae Herba, Zingiberis Rhizoma, Rhei Rhizoma, Paeoniae Radix, Atractylodis Rhizoma, and Forsythia Fruit are reported to possess antibacterial activity [41][42][43][44][45][46][47][48]. Here, the total number of bacteria was estimated by qPCR to assess the possible influence of BTS on bacterial count.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial activity of BTS is one possible mechanism. Among BTS components, Menthae Herba, Zingiberis Rhizoma, Rhei Rhizoma, Paeoniae Radix, Atractylodis Rhizoma, and Forsythia Fruit are reported to possess antibacterial activity [41][42][43][44][45][46][47][48]. Here, the total number of bacteria was estimated by qPCR to assess the possible influence of BTS on bacterial count.…”
Section: Discussionmentioning
confidence: 99%
“…There were statistically significant differences ( p < 0.05) in the pharmacokinetic parameters of the five bioactive constituents, T max , C max , AUC 0– t , MRT 0 − t , CLz and t 1/2 between the MDMD and NMDMD groups. Previous studies have reported that aloe‐emodin, paeoniflorin and amygdalin are bioactive constituents of rhubarb, moutan bark and Prunus persica (Cao et al, ; Xiang et al, ; Jang et al, ; Tao et al, ; Shun‐xing et al, ), respectively. These findings may suggest that mirabilite could assist paeoniflorin and amygdalin absorption into blood when used together with rhubarb, moutan bark and Prunus persica .…”
Section: Resultsmentioning
confidence: 99%
“…These therapeutic effects are attributed to the main bioactive constituents of DMD. Modern pharmacological studies have revealed that emodin, aloe‐emodin, rhein, paeoniflorin and amygdalin in DMD have extensive anti‐inflammatory and antioxidant activities (Cao et al, ; Xiang et al, ; Jang et al, ; Tao, Wen, Song, & Wang, ; Shun‐xing, Nan‐sheng, & Feng‐ying, ; Lin & Lin, ). According to plasma pharmacochemistry, only the constituents absorbed into blood may have the chance to perform pharmacological bioactivities (Han et al, ; Tang, Wang, Liu, Cheng, & Xiao, ).…”
Section: Introductionmentioning
confidence: 99%
“…Rhubarb has the effects of promoting dampness and relieving jaundice (17), anti-inflammatory activity, kidney protection, preventing and treating high blood lipids and cholestasis, ameliorating fibrosis and hepatic encephalopathy, and promoting blood circulation and hemostasis (18). Anthraquinones are the active constituents of rhubarb, and they include rhein, emodin, chrysophanol, emodin methyl ether, and aloe-emodin (19); meanwhile, studies have indicated that rhein shows a higher bioavailability and is more easily absorbed and exposed than other anthraquinones (20,21).…”
Section: Meanwhile the Rhubarb Cultivation Area In The Unitedmentioning
confidence: 99%